(3Ydd GdMOjKs - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3jHJOF Hbhdg hSFd Yf MOjK YGeQ Hf SYO Gdjefi Yf CHj HcQ GdUOjb ai bhdg JYGdi dYRjR (B( (3CMSfhG GdMSfi hRjGOI s
(3BNQgG (B:s
(3jfJgi Hbhdg hSFd Yf MOjK YHO GdQMef Hf SCHW Yf CHj HcQ Yf GdfHi Udi Gddg Ydjg hSde bGd (B( (3UfaGf ef CeJi (B) s
(3GdhQb eVWQH ai GdJLdjOs
(3HgG fXGe GdJYbjHIs
(3ajg Ydd GdeSfO ef HbjI eSfO CHj HcQ GdUOjb hChd eSfO YeQ Hf GdNWGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1159s
Keywords: (3GdMOjK h GdeUWdMs